Research on higher education in Europe - Teichler, Ulrich (European Journal of Education, 2005)
Research on higher education grew in European countries from scattered individual activities towards a certain degree of visibility in the 1970s, largely as consequence of growing public problem awareness. In the 1980s, it experienced a set-back due to declining public interest in higher education as a key issue of societal policies. From the late 1980s onwards, research in this domain again drew attention and support in the wake of debates about the knowledge society, new modes of steering and management and the increasing internationalisation of higher education. However, growth and consolidation of this research were accompanied by a more rapid growth of policy-geared information collection and dissemination in the framework of evaluation, consultancy, expert commissions and the daily work of the growing number of higher education professionals. Research on higher education often does not have a solid institutional base and it both benefits and suffers from the fact that it is a theme-base area of research, drawing from different disciplines, and that the borderline is fuzzy between researchers and other experts on higher education. But a growth and quality improvement of research on higher education can be observed in recent years — certainly to some extent due to growing cooperation of researchers across Europe and to increasing cooperation in comparative projects. In the future, the first steps undertaken to establish study programmes for higher education experts could turn out be beneficial not only for the dissemination of research findings, but also for the quality of young researchers in this domain.
Keywords: Europe; utilisation des recherches